2013
DOI: 10.1007/s00204-013-1021-9
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induced by Trimethyltin chloride in human neuroblastoma cells SY5Y is regulated by a balance and cross-talk between NF-κB and MAPKs signaling pathways

Abstract: Trimethyltin chloride (TMT) has been known as a classic neurotoxicant which can cause serious neuronal degeneration diseases. Nuclear factor κB (NF-κB) and mitogen-activated protein kinases (MAPKs) signaling pathways play pivotal role in the central nerves system. In the present study, the intracellular pathways involved in TMT-induced apoptosis on human neuroblastoma cells SY5Y (SH-SY5Y) were investigated. We observed high level of nuclear NF-κB p65 submit, activated JNK, ERK, and p38 by TMT exposure. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Recent studies have demonstrated that ROS-dependent NF-kB activation induced the protein expression of c-Myc and Noxa in p53-independent human NSCLC cell death [50]. On the contrary, NF-kB activation was involved in resistance to oxidative stress and p53-mediated programmed cell death [5153]. Therefore, we investigated whether this transcription factor may play a role in artocarpin-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that ROS-dependent NF-kB activation induced the protein expression of c-Myc and Noxa in p53-independent human NSCLC cell death [50]. On the contrary, NF-kB activation was involved in resistance to oxidative stress and p53-mediated programmed cell death [5153]. Therefore, we investigated whether this transcription factor may play a role in artocarpin-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of apoptosis was performed using an Annexin-V-FITC/propidum iodide (PI) apoptosis kit as described previously [51]. Following treatment with artocarpin with or without inhibitors, cells were labeled with Annexin-V and PI, and then evaluated by a flow cytometer.…”
Section: Methodsmentioning
confidence: 99%
“…In a model of TMT-induced neurodegeneration, Casalbore et al (2010) showed that phosphatidylinositol 3-kinase (PI3K)/Akt and ERK1/2 activation, triggered by BDNF overexpression, attenuated the TMT-induced neurotoxicity in NSCs. In contrast, a recent study by Qing et al (2013) reported that pre-treatment with the MEK-ERK1/2 inhibitor U0126 reduced TMT-induced apoptosis in human neuroblastoma SY5Y cells via upregulation of survival factors, Bcl-2 and XIAP, suggesting that ERK signaling may play a role in neuronal cell death. In the present study, we observed that ERK1/2 was markedly activated in the mouse hippocampus following TMT treatment, although the temporal expression tendency was differently observed within each subregions of the hippocampus.…”
Section: Discussionmentioning
confidence: 75%
“…We hypothesized that this process might involve crosstalk between NF-kB and the JNK signaling pathway. In the human neuroblastoma cell line SY5Y, NF-kB inhibition exaggerated the phosphorylation of JNK mediated by trimethyltin chloride [26]. Gancz et al reported that p65 silencing by RNAi abrogated complement-induced JNK activation in HeLa cells [27].…”
Section: Discussionmentioning
confidence: 99%